Pembelajaran Inovatif Aswaja An-Nahdliyah dalam Mengasah Pemahaman dan Amaliyah Aqidah Asy’ariyah - Ummu Qurratu Aini; Asriana Kibtiyah (MANAZHIM, 2023)
This article aims to describe how Aswaja an-Nahdliyah teachers implement innovative learning methods, teaching materials and learning media in order to hone understanding and amaliyah aqidah Asy'ariyah students at MTs Salafiyah Siman Lamongan with the aim that the learning atmosphere is not monotonous, boring and makes students saturated, but on the contrary, students are actively creative and can achieve learning goals. This research is a case study qualitative research conducted at MTs Salafiyah Siman Lamongan, research data will be obtained from principal informants, Aswaja teachers and students. Data collection techniques through interviews, observation and documentation, then data analysis techniques using domain, taxonomy, and componential analysis. While the data validity technique is by extending presence and triangulation. The results showed that the innovative learning implemented by the Aswaja an-Nahdiyah teacher was by using a combination of the lecture method and the integration of aqidah with mathematics, the analytical method, the inquiry method and the active debate method. The teaching material is from the NU book Aswaja published by LP. Ma'arif NU East Java which was developed using classic Islamic boarding school books and trusted online NU sites, with LED TV learning media, projectors, YouTube social media, origami paper, and markers.